Study on control method for fast neutral section passing of high-speed EMUs - LIU Jun (机车电传动)
This paper proposed a method to control neutral section passing based on the signal fusion of catenary voltage amplitude and phase, from a study on the neutral section passing process and optimal closing time for the vacuum circuit breaker on high-speed EMUs, to solve the downsides of the traditional control method for neutral section passing, i.e. a long vacuum circuit breaker disconnection duration and serious power loss. This method focused on the judgment whether a high-speed EMU has passed a neutral section depending on changes in the catenary voltage amplitude and phase. In order to verify the effectiveness of the proposed method, a semi-physical test was performed. Based on the test results, any changes in the catenary voltage amplitude and phase occurring when an EMU enters an electrified section can be quickly and effectively identified using the proposed method, so that the vacuum circuit breaker can be closed effectively ahead of time the EMU passes a neutral section, reducing the neutral section passing duration by more than 25%. Confronting the deficient railway capacity in China and the complicated track conditions, the method proposed in this paper can effectively reduce the power loss in the process of neutral section passing, so as to improve the efficiency of railway operation and relieve the traffic pressure during the peak period of passenger transportation, exhibiting a promising engineering application prospects.